INFORMATIVE TEXT TRANSLATION INTO ENGLISH TO INDONESIAN - Lina Anisah (Universitas Sembilanbelas November Kolaka, 2016)
The purpose of this study is to obtain an overall picture of the translation of informative text from English to Indonesian. The translation is then measured in terms of translation.This study used a qualitative approach using content analysis method. Object of this study is informative text from English to Indonesian translated by the fifth semester English students of University of Borobudur. The translation then is analyzed based on four sub-focus, which are equivalence, strategy, errors, and the factors that cause errors in translationIn the translation process that is done by the students found the equivalence translation is widely used by the students, and the translation strategies are also widely used by the students. However, there are also many errors in their translation. So the researchers also analyzed the factors that cause the errors. Therefore, students need to be taught translation learning in order to produce good quality translations. Not only can generate good translation of informative text, but also a variety of other texts